Comparative Analysis Of The Profitability Of PT. Bank Panin Syariah Securities Before And After Going Public - Hardana, Ali; Sahri, Mohammad Zahrudin; Ramadhan, Ahmad (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
The approach taken with the theories put forward is related to the profitability ratios including Return On Assets (ROA), which is used as an indicator to measure a company's ability to carry out company operations. While the profitability ratio Return On Equity (ROE) that can be used as an indicator to measure the ability of the company's equity in obtaining net income available to shareholders of the company. This research is a quantitative research using comparative analysis. the type of data used is secondary data in the form of company financial statements obtained from the company's official website, namely www.anualreport.co.id in 2010-2019. The research sampling method used saturated sampling.The results of this study indicate that there is no significant difference between the profitability ratios before and after going public at PT. Bank Panin Syariah Sekuritas in this case is seen from the indicators of Return On Assets (ROA) and Return On Equity (ROE). Keywords: Profitability Ratio, Performance, go public.